Posttraumatic Growth in Women who have Experienced Loss of a Child. Issue 5 (September 2021) - Doherty, Mary Ellen; Scannell-Desch, Elizabeth
Abstract: Purpose: The purpose of this study was to describe and explore the experiences of women who have lost a child and the degree of posttraumatic growth revealed by the experiences. Study Design and Method: A qualitative descriptive study was conducted with interviews of mothers and grandmothers of children who died using the posttraumatic growth framework. Findings: Participants included 11 mothers and 2 grandmothers. The posttraumatic growth framework was useful in examining their experiences. Seven themes were identified through data analysis: When my child died, I lost part of myself; Anticipated loss versus unanticipated loss; Picking up the pieces of my life; Support, kindness, and compassion helped; Moving on while still broken; Never forgotten, always in my heart; and Holding my loved ones close . Clinical Implications: Nurses are in strategic positions to help women who have experienced the loss of a child by building rapport, establishing trust, and demonstrating empathy. Abstract : Using posttraumatic growth as a framework, researchers in this qualitative study of 11 women who experienced the death of a child or grandchild, identified seven common themes. The women were forever changed by the death of the child and appreciated compassion and support from health care professionals, friends, and family members. These data highlight the uniqueness of every loss and the needs of each person experiencing the loss. Findings emphasize the importance of listening to women and being receptive to posttraumatic growth.